2021
DOI: 10.1111/febs.15904
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of transcription and processing of tRNA

Abstract: Coordination of transcription and processing of RNA is a basic principle in regulation of gene expression in eukaryotes. In the case of mRNA, coordination is primarily founded on a co-transcriptional processing mechanism by which a nascent precursor mRNA undergoes maturation via cleavage and modification by the transcription machinery. A similar mechanism controls the biosynthesis of rRNA. However, the coordination of transcription and processing of tRNA, a rather short transcript, remains unknown. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 169 publications
(299 reference statements)
0
16
0
Order By: Relevance
“…Is the native-nonnative equilibrium dependent on spatiotemporal gene expression and cellular cofactors? Second, while our studies were performed with in vitro transcripts, it would be informative to examine how other cellular events, such as cotranscriptional RNA folding and modification (8,43,44), affect the conformational sampling of tRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Is the native-nonnative equilibrium dependent on spatiotemporal gene expression and cellular cofactors? Second, while our studies were performed with in vitro transcripts, it would be informative to examine how other cellular events, such as cotranscriptional RNA folding and modification (8,43,44), affect the conformational sampling of tRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the intron is just one of many tRNA processing events and it remains unclear if tRNA splicing is coordinated with tRNA transcription, processing, and/or modification [reviewed in Jarrous et al (2021)]. Following transcription, by RNA Pol III nascent intron‐containing pre‐tRNAs are processed by three nucleases including the TSEN complex, RNase P, and RNase Z and there is growing evidence that suggests co‐transcriptional tRNA processing is occurring [reviewed in Jarrous et al (2021)]. tRNAs are the most heavily post‐transcriptional modified RNAs inside the cell and dysregulation of these modifications has been linked to neurological disease [reviewed in Das et al (2021) and Suzuki (2021)].…”
Section: Conclusion and Open Questions In Transfer Rna Splicingmentioning
confidence: 99%
“…There are several groups of enzymes involved in tRF biogenesis. The 5′ leader sequence is a substrate for RNase P, producing the mature 5′ end of tRNA, while nuclease Z cleaves the 3′ trailer [ 19 , 20 ]. Moreover, it was suggested that the Dicer nuclease produces tRF-5 and tRF-3 fragments of a size similar to that of miRNA, i.e., 20–25-nucleotide long oligomers, which are cut by Dicer at the tRNA elbow end [ 18 ].…”
Section: Introductionmentioning
confidence: 99%